Alcohol Consumption as a Risk Factor for Atrial Fibrillation: a Systematic Review and Meta-Analysis - Samokhvalov, Andriy V. (2010)
BACKGROUND: Alcohol exposure is one of the major risk factors for global burden of disease, but atrial fibrillation (AF) had not yet been included in these estimates. The purpose of this contribution was to examine the dose-response relationship between alcohol consumption and AF and to explore potential causal pathways. DESIGN AND METHODS: Systematic literature review and meta-analyses RESULTS: Overall, a consistent dose-response relationship between the amount of alcohol consumed daily and the probability of the onset of AF was found. Women consuming 24, 60, and 120 grams of alcohol daily had RRs of 1.07 (95% CI: 1.04,1.10), 1.42 (95% CI: 1.23,1.64) and 2.02 (95% CI: 1.60,2.97) respectively, relative to non-drinkers. Among men, the corresponding RRs were 1.08 (95% CI: 1.04,1.11), 1.44 (95% CI: 1.23,1.69) and 2.09 (95% CI: 1.52,2.86). Based on the categorical analyses, we could not exclude the existence of a threshold (3 drinks a day for men and 2 drinks a day for women). Several pathogenic mechanisms for the development of atrial fibrillation in alcohol users were identified. CONCLUSIONS: Epidemiological criteria for causality were met to conclude a causal impact of alcohol consumption on the onset of AF with a monotonic dose-response relationship. However, the impact of light drinking is not clear.